Climate, radial growth, and mortality associated with conifer regeneration infected by root disease (Armillaria ostoyae) - Michael P. Murray; Adrian Leslie (The Forestry Chronicle)
Tree root disease caused by the pathogen Armillaria ostoyae (Romagn.) Herink has notable influence on bio-economic systems of southern British Columbia (BC) and the northwestern United States. Annual radial growth and mortality trends of regeneration associated with A. ostoyae during the first 21 years of a plantation were investigated. Our dendrochronological approach focused on a plantation established in 1991 with Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), western larch (Larix occidentalis Nutt.), and lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm. ex S. Wats.). We examined tree rings for reduced growth onset (RGO) to estimate infection periods. Among trees studied, we found that the number of RGO events peaked in 2006 followed by a steady decline in frequency. A similar trend was seen in annual mortality rates which reached maximum values in 2007 followed by an uninterrupted decrease. The average number of years from RGO to death based on host species ranged from 2.3 to 3.6 years. According to on logistic regression modeling, values associated with drought codes and duff moisture codes were significant in determining the year of death for infected trees. The predicted increase in frequency of summer droughts may lead to elevated mortality associated with A. ostoyae in young plantations.